EFEKTIFITAS PAKET ASI (EDUKASI KESEHATAN : LAKTASI DAN PIJAT OKSITOSIN) TERHADAP PRODUKSI ASI IBU PRIMIPARA - Ulva Noviana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Breast Milk (ASI) is the most perfect food for the baby, where the nutritional content in accordance with the need for intelligence. Breast milk contains antibody substances that are useful for preventing infectious bowel disease and optimal digestion of growth and development. Based on the preliminary study of November 2017 on 10 primiparous postpartum women, there were 7 postpartum mothers producing less milk. The objectives of the study analyzed the differences in breast milk production in postpartum women before and after being given a successful breastfeeding package This study used pre experimental design with one group pretest postest model of independent variables Package "Sukses ASI" and the dependent variable was milk production. The population of this study were 20 primiparous postpartum women and the samples were 19 primiparous mothers using random sampling technique. The results showed that most of the Asylum production mothers were less than before the "Successful Breastfeeding" package with mean of 4.21 and most of Asi's postpartum mothers were fluent after being given the "Successful Breastfeeding" package with mean of 7.89. Based on statistical test with paired ttest obtained p value = 0.000, where this value is smaller than alpha 0,05 so H1 was accepted, meaning that there was difference of milk production before and after given packet of success of ASI It is expected to provide inputs for health workers to increase breastfeeding production in primiparous postpartum mothers. This package will be more effective if the delivery of health education not only with edge leafleat by using video. For the people of this "Successful Breastfeeding" package people can become aware of the importance of breastfeeding.